Analisis Kedalaman Gerusan Lokal (Local Scouring) di Hilir Bangunan pelimpah (Stepped Modified Spillway) dengan Model Fisik 2D - kuncoro, wahyu hadi; Wahono, Endro Prasetyo; Zakaria, Ahmad; Kusumastuti, Dyah Indriana (Universitas Lampung, 2021)
Spillway is a hydraulic structure whose existence is very important because it is built to release excess water or flood discharge that cannot be accommodated in the dam. The hydraulics analysis of this study used a spillway design (Stepped modified Spillway) with a 2-D physical model and the sediment used was sand with a uniform diameter of 1.8 mm or passed sieve no. 16. This research was carried out 5 times for every 25 minutes of upstream water level observations.In the Stepped spillway spillway the maximum scour (dsmax) occurs at an upstream height (H0) of 3 cm of 0.125 m with an Lds of 0.09 m from the downstream of the spillway. Meanwhile, for the Stepped Modified Spillway spillway, the maximum scour (dsmax) occurs at an upstream height ( H0) 3 cm is 0.076 m with Lds of 0.221 m. This shows that the greater the flow rate, the greater the depth of scour that occurs. So it can be concluded that the Lacey method is the closest to the laboratory results. This is because a balance has been achieved. The deeper the local scour that occurs, the more volume of sediment carried downstream of the weir.Keywords: Stepped and stepped modified spillway, local scour, sediment.